Personal Branding Psikolog Seto Mulyadi (Kak Seto) di Era Disrupsi Media - Rina Juliastuti; Denik Iswardani Witarti (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2020)
The rapid technological development has made social media much sought-after in the public. Social media has been widely used in building personal branding. But this is not the case with child psychologist Kak Seto who has no personal account in any of social media platforms, while his activities in the world of children always become an attraction and have news value. The formulation of the problem in this research is how the personal branding of Kak Seto in the era of media disruption. The purpose of this research is to explain the activities of Kak Seto in the context of